Preload loss of high-strength bolts in friction connections considering corrosion damage and fatigue loading. (July 2022) - Jiang, Chao; Xiong, Wen; Cai, C.S.; Zhu, Yichen; Wang, Jia
Highlights: The preload change of bolts after installation was measured on the double lap friction connections. The corrosion effects on the bolt preload loss were investigated based on the connections with four corrosion levels. The bolt preload loss considering the combined action of corrosion damage and fatigue loading was analyzed. Abstract: The preload loss of high-strength bolts in friction connections was investigated considering the corrosion damage and fatigue loading. Double lap connections were assembled and the ultrasonic measurement method was employed to obtain the real-time preload of the bolts. Accelerated corrosion tests of specimens were used to achieve four corrosion levels and the and the corresponding weight loss ratio of the specimens varied from 0 to 10.1%. Fatigue test was then performed on eight corroded connections. The preload change of bolts after installation, corrosion tests, and certain number of load cycles was measured. It is found that the corrosion effects on the bolt preload loss was significant, and an average value of 41.2% preload loss was observed for specimens of 10% weight loss. The influence of fatigue load on the preload loss after unloading could be ignored, but the combination of tensile loading, fatigue loading, and corrosion damage could lead to an up to 11% preload loss.